2015
DOI: 10.1590/1678-4499.0363
|View full text |Cite
|
Sign up to set email alerts
|

Perdas e custos associados à erosão hídrica em função de taxas de cobertura do solo

Abstract: The aim of this study was to estimate water erosion costs associated with nutrient losses in four different rates of artificial cover. The experiment was carried out from 1987 to 1996 in runoff plots to measure soil losses in Campinas, State of Sao Paulo, in an Ferralsol under natural rainfall. The experimental design was completely randomized, with four treatments (0%, 24%, 40% and 90% artificial cover) and three replications. To estimate costs, P, K + , Ca 2+ and Mg 2+ concentrations in runoff water and soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
34

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 37 publications
2
26
0
34
Order By: Relevance
“…Taking into account that P is potentially the element causing eutrophication of surface waters, the likely place of deposition of fine sediments carried by water erosion (Shigaki et al, 2007), this is a serious problem. Moreover, it is important to consider that losses of P, other elements, and OM by water erosion are responsible for soil depletion and increased cost of agricultural production (Dantas and Monteiro, 2010;Dechen et al, 2015).…”
Section: Total Losses Of P K Ca Mg and Organic Matter (Om) And Thmentioning
confidence: 99%
See 4 more Smart Citations
“…Taking into account that P is potentially the element causing eutrophication of surface waters, the likely place of deposition of fine sediments carried by water erosion (Shigaki et al, 2007), this is a serious problem. Moreover, it is important to consider that losses of P, other elements, and OM by water erosion are responsible for soil depletion and increased cost of agricultural production (Dantas and Monteiro, 2010;Dechen et al, 2015).…”
Section: Total Losses Of P K Ca Mg and Organic Matter (Om) And Thmentioning
confidence: 99%
“…In studies carried out in other countries, it was shown that the total cost of these losses was higher in CT than in NT (Hart et al, 2004). In Brazil, some studies showed that this value was greater in NT than in CT (Bertol et al, 2007b), others showed the opposite (Dantas and Monteiro, 2010), and others showed that increased soil cover decreased the amount of losses (Dechen et al, 2015), thus establishing a contradiction. Knowledge of the cost of nutrient losses through erosion is important in helping convince farmers to adopt effective conservation practices to reduce erosion and its cost.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations